Temporal and Spatial Pattern of Holcoglossum Schltr. (Orchidaceae), an East Asian Endemic Genus, Based on Nuclear and Chloroplast Genes - Zhao, Jiahong; Zhou, Peng; Li, Xiaoqian; Zhang, Liguo; Jin, Xiaohua; Xiang, Xiaoguo (Frontiers in Ecology and Evolution, 2020)
East Asia is characterized by high levels of species diversity and endemism. However, the biogeographic patterns and processes of endemic epiphytic plants within East Asia are still poorly known. In this study, we used eleven plastid and one nuclear DNA sequences to infer the historical biogeography of Holcoglossum Schltr. (Orchidaceae), an eastern Asian endemic genus. Phylogenetic analyses strongly support Holcoglossum as monophyletic, and contains three major clades (TC, HC and AC). Our results suggest that the most recent common ancestor of Holcoglossum occurred in Palaeotropical region in the late Miocene (6.29 Ma). Within Asian mainland, three dispersal and one vicariant events were hypothesized to explain the expansion of Holcoglossum from Palaeotropical region to Sino-Himalayan and Sino-Japanese region. These events occurred in the latest Miocene to middle Pleistocene, which may be associated with the uplift of the southeastern Tibetan Plateau and intensification of East Asia monsoon around that period. A disjunct distribution between Asian mainland and Taiwan was inferred in the latest Pliocene-early Pleistocene, which supports the close floristic affinity between Taiwan and Asian mainland. This study contributes to our knowledge on the historical biogeography of endemic epiphytic plants in East Asia.